2015
DOI: 10.1080/01596306.2015.1061979
|View full text |Cite
|
Sign up to set email alerts
|

Being ‘nice’ or being ‘normal’: girls resisting discourses of ‘coolness’

Abstract: In this paper we consider discourses of friendship and belonging mobilised by girls who are not part of the dominant 'cool' group in one English primary school.We explore how, by investing in alternative and, at times, resistant, discourses of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 27 publications
2
21
0
Order By: Relevance
“…Involvement in bullying, even through reinforcing acts such as laughing, can thus be understood as a means through which pupils are able to position themselves and others within the peer group (Dixon, Smith, and Jenks 2008;Gini 2006;Thornberg 2015b) and thus as a way of defining their own social selves (Jacobson 2010). In this sense, then, the pupils can be understood to be engaging in positioning work (Adler and Adler 1995;Currie, Kelly, and Pomerantz 2007;Duncan 2004;Eder 1985;Owens, Shute, and Slee 2000;Paechter and Clark 2016), whereby their efforts are focused on positioning themselves favourably among their peers, rather than simply seeking to cause harm to those being bullied.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Involvement in bullying, even through reinforcing acts such as laughing, can thus be understood as a means through which pupils are able to position themselves and others within the peer group (Dixon, Smith, and Jenks 2008;Gini 2006;Thornberg 2015b) and thus as a way of defining their own social selves (Jacobson 2010). In this sense, then, the pupils can be understood to be engaging in positioning work (Adler and Adler 1995;Currie, Kelly, and Pomerantz 2007;Duncan 2004;Eder 1985;Owens, Shute, and Slee 2000;Paechter and Clark 2016), whereby their efforts are focused on positioning themselves favourably among their peers, rather than simply seeking to cause harm to those being bullied.…”
Section: Discussionmentioning
confidence: 99%
“…The peer group is thus seen to play a central role in how individuals react to the aggressive behaviour of others. Peers who witness a bullying incident but are not directly involved as 'bullies' or 'victims' have been categorised as 'bystanders', whose reactions to the bullying may influence the situation in different ways (Hawkins, Pepler, and Craig 2001; 'mean' and contrasted with 'niceness' and 'goodness' (Paechter and Clark 2016). This suggests that rather than simply engaging in bullying in order to cause harm, pupils may engage in bullying as a means through which to gain friends and increase their social status (Burns et al 2008;Frisén, Jonsson, and Persson 2007;Juvonen and Graham 2014;Juvonen, Wang, and Espinoza 2013;Thornberg 2010b;Thornberg and Knutsen 2011).…”
mentioning
confidence: 99%
“…Paechter employed the Foucaultian perspective (Foucault 1980(Foucault , 1982 that power relations are fluid and constantly contested, and that where there is power there is resistance, to explore this relationship dynamic in an educational context. Across several studies, Paechter demonstrated that hegemonic girls 2 did not perform the male-focused 'emphasised femininity' described by Connell (1987), but rather exercised independence and maintained a constant resistance to their subservient position (see Paechter, 2007;2018;Paechter & Clark 2015).…”
Section: Single-sex/co-educational Schoolsmentioning
confidence: 99%
“…Hegemonic girls were found to mobilise considerable resources in establishing an oppositional counter-discourse to the Gramscian hierarchy of gender-identities, and were also found to be capable of exercising considerable power with regard to non-hegemonic boys as well as girls (Paechter, 2007;2018;Paechter & Clark, 2015;Renold, 2005). However, across the aforementioned studies, it was consistently found that hegemonic girls were simply unable to compete with hegemonic boys and were quickly sanctioned for any perceived challenges to the boys' dominance.…”
Section: Single-sex/co-educational Schoolsmentioning
confidence: 99%
“…Blaise 2005;Martin 2011;Paechter 2007;Renold 2005;Skelton and Francis 2003). In particular, it builds on several key findings; that young children in school navigate a complex and sometimes even contradictory repertoire of gendered identities, including multiple gendered identities (Allan 2009;Renold 2004), that young students can and will strategically employ multiple identities, sometimes simultaneously and other times enacting different identities for different contexts or at different times (Paechter and Clark 2015), and that it is crucial to understand what such identities mean for the children who enact them, particularly if one is interested in the broader implications of this on identity politics and gendered norms (Paechter 2012). Paechter (2012) voices an important caution against presuming that certain typical, 'dominant' forms of masculinity are necessarily hegemonic in that they work to subordinate girls and women.…”
Section: The Social Life Of Rights and Gender Identities In Primary Smentioning
confidence: 99%